Potential of Secondary Metabolites from Acriopsis liliifolia Leaves as a Tyrosinase Inhibitor: Docking Study - Khoeriyah, Ni'matul; Wannawijaya, Nashwa Maheswari; Apsari, Cintya Nurul; Nuraini, Latifa (Universitas Tidar, 2024)
The demand of natural chemicals with high effectiveness and low side effects increases plant exploration, including in the cosmetic and pharmaceutical fields. Trend of skin-lightening products is in great demand, causing its development to overgrow. Acriopsis liliifolia is an orchid species commonly found in Java and its leaves contain many secondary metabolites, thus attracting attention to be studied its potential as a tyrosinase inhibitor to overcome hyperpigmentation. This study explores potential of secondary metabolites in A. liliifolia leaves as tyrosinase inhibitors through microchemical tests, secondary metabolite profiling with LC-HRMS, and docking study using MOE. The results of the microchemical test showed that this orchid contains flavonoid, phenolic, terpenoid, and alkaloid compounds. Secondary metabolite profiling with LC-HRMS produced 130 compounds, then 15 of the most potential compounds were selected. The docking study showed that prolylleucine had lowest S score of -8,738 kJ/mol, lower than native ligand, kojic acid. This indicates that prolylleucine has a significant binding affinity to tyrosinase enzyme receptor through twelve bonds on the active site of enzyme. Prolylleucine can be used as a lead compound for further testing. Keywords: Acriopsis liliifolia, secondary metabolites, leaves, tyrosinase inhibitor, molecular docking.